2013
DOI: 10.1080/09540121.2013.855699
|View full text |Cite
|
Sign up to set email alerts
|

Improved virological suppression in children on antiretroviral treatment receiving community-based adherence support: A multicentre cohort study from South Africa

Abstract: Adherence to antiretroviral treatment (ART) is a challenge in childhood, and children on ART have reduced virological suppression compared to adults. This study evaluated the effect of community-based adherence support (CBAS) on virological outcomes amongst children receiving ART in four South African provinces. Patient Advocates are lay CBAS workers who provide adherence and psychosocial support for patients, undertaking home visits to address household challenges affecting adherence. Patient Advocates provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…In another study from the USA, only 50.5% of youth, aged 12-24 years, had virological suppression, despite reporting good adherence [73]. A study from South Africa reported on virological suppression rates of between 55 and 65%, depending on whether or not the children received community-based adherence support [74]. Of note, they found that virological suppression was lower in children <2 years of age.…”
Section: Adherence and Viral Load Suppressionmentioning
confidence: 89%
“…In another study from the USA, only 50.5% of youth, aged 12-24 years, had virological suppression, despite reporting good adherence [73]. A study from South Africa reported on virological suppression rates of between 55 and 65%, depending on whether or not the children received community-based adherence support [74]. Of note, they found that virological suppression was lower in children <2 years of age.…”
Section: Adherence and Viral Load Suppressionmentioning
confidence: 89%
“…This reinforces calls for early diagnosis and early ART initiation to reduce paediatric morbidity and mortality [39]. Furthermore, systems to flag high VL results are needed and adherence, crucial to achieving and maintaining viral suppression, must be reinforced – ongoing counselling must be provided from the time of ART initiation to address children's changing adherence barriers, and community-based adherence support should be considered with community workers providing education and psychosocial support to address household challenges impacting on adherence [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…About 20 % of the children received community-based adherence support, which included home visits by patient advocates to provide psychosocial support and address contextual household challenges affecting adherence. A significant difference in rates of virologic suppression was found: 65.6 % among those who received the intervention compared to just 55 % among those who did not [30]. …”
Section: Principles Of Community-based Therapymentioning
confidence: 99%